2014
DOI: 10.1055/s-0034-1378942
|View full text |Cite
|
Sign up to set email alerts
|

Novel (+)-3-Carene Derivatives and Their Application in Asymmetric Synthesis

Abstract: A simple synthetic procedure for the preparation of mono-N-tosylated-1,2-diamines derived from (+)-3-carene is described. (+)-3-Carene is transformed into the corresponding N-tosylaziridine derivative using chloramine-T trihydrate. Subsequent ring opening with sodium azide followed by reduction of the azide function gives the optically pure mono-N-tosylated-1,2-diamine. This ligand is effective in asymmetric transfer hydrogenations of aromatic ketones. It can also be transformed into other chiral ligands by al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Furthermore, the results obtained with our complexes, indicated that the steric hindrance around the Ru center in the transition state, deriving both from the ligand and the substrate, could affect the reactivity and the enantioselectivity of the reactions. 27,37 In summary, the best result in terms of reaction rate and enantioselectivity was obtained with complex A in the reduction of the activated ketone substrate 4f, ethyl 3-oxo-3phenylpropanoate (entry 22).…”
Section: N-(3r4r)-3-[(s)-2-(aminomethyl)pyrrolidin-1-yl]-1-benzylpipmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the results obtained with our complexes, indicated that the steric hindrance around the Ru center in the transition state, deriving both from the ligand and the substrate, could affect the reactivity and the enantioselectivity of the reactions. 27,37 In summary, the best result in terms of reaction rate and enantioselectivity was obtained with complex A in the reduction of the activated ketone substrate 4f, ethyl 3-oxo-3phenylpropanoate (entry 22).…”
Section: N-(3r4r)-3-[(s)-2-(aminomethyl)pyrrolidin-1-yl]-1-benzylpipmentioning
confidence: 99%
“…As confirmed by 1 H-NMR and ESI spectroscopy investigations two different complexes A and B were formed bearing a bidentate or tridentate ligand. [26][27][28] In the 1 On the contrary, in the presence of TEA and toluene, the tridentate complex B is obtained as evinced by the absence of the peaks belonging to p-cymene group in the 1 H-NMR spectrum. Satisfactory elemental analyses and ESI-MS data corresponding to the proposed structures were obtained for both complexes.…”
Section: Introductionmentioning
confidence: 98%